Strategy Implementation to Maintain service Quality in Chain and Non-Chain Hotels and Resorts in Phuket - Supphakan Wattanasantikul (Prince of Songkla University, 2019)
Thesis (M.B.A., Hospitality and Tourism Management (International Program))--Prince of Songkla University, 2018